2022
DOI: 10.1109/access.2022.3168656
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Auditory Effects Among U.S. Government Personnel Reporting Directional Audible and Sensory Phenomena in Havana

Abstract: The mysterious incidents on diplomatic and intelligence personnel began in 2016. Since then, nearly 200 incidents have been reported. The illnesses and symptoms are called Havana Syndrome, named for the city where cases were first reported. The initial accounts from Havana include hearing of loud highpitched sounds, localizing the sources as coming from above or behind the head, experiencing a directional sound that ceases if one steps away, the covering of ears not making any difference, some hearing the soun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…After considering a wide variety of possible mechanisms, both studies concluded that some of the cases with abrupt-onset, location-dependent sensory phenomena could be plausibly explained by exposure to directed, pulsed radiofrequency energy, despite important uncertainties. Others have also pointed to pulsed radiofrequency energy as a plausible mechanism . The US Intelligence Community has discounted this possibility and concluded that reported symptoms were probably the result of “preexisting conditions, conventional illnesses, and environmental factors,” influenced by their assessment that no foreign adversary played a role in these cases .…”
mentioning
confidence: 99%
“…After considering a wide variety of possible mechanisms, both studies concluded that some of the cases with abrupt-onset, location-dependent sensory phenomena could be plausibly explained by exposure to directed, pulsed radiofrequency energy, despite important uncertainties. Others have also pointed to pulsed radiofrequency energy as a plausible mechanism . The US Intelligence Community has discounted this possibility and concluded that reported symptoms were probably the result of “preexisting conditions, conventional illnesses, and environmental factors,” influenced by their assessment that no foreign adversary played a role in these cases .…”
mentioning
confidence: 99%
“…Although the required peak power densities are high, they are achievable with existing high-power commercial and military microwave systems operating under pulsed conditions [5]. The disclosure comes as somewhat of a surprise to some, although it has been stipulated previously [6], [7]. Significantly, they also fall within the permissible "safe" limits of currently promulgated safety standards and protection guidelines.…”
mentioning
confidence: 99%